RECOMMENDATIONS TOWARDS SUSTAINABLE FARMING METHOD FOR AN ORGANIC VEGETABLE PRODUCTION IN BUKIDNON, PHILIPPINES - Joemar Dayham Javier; Maria Pia M Sison (Agricultural Socio-Economics Journal, 2023)
There are various methods or practices for sustainable farming. This study recommends farming methods that are appropriate and effective for organic vegetable production in Bukidnon and, in some way, serve as the basis for sustainable farming. Thus, this paper aims to recommend a sustainable farming method for organic vegetable production. Results of the study revealed that the organic focal person-key informants would highly recommend farming practices such as crop rotation, and intercropping for crop planning and management, composting, green manures and animal manure for nutrient management, pest and disease management, weed management, soil cultivation and tillage, plant propagation such as traditional varieties and seed conservation, and diversified farming system. As reported, there are no specific local markets for organic products in Bukidnon, as well as international markets. Among the issues and concerns raised by the key informants, organic certification is the topmost issue. This issue set a little drawback and discouraged some farmers from going organic. Recently, the senate in the Philippines finally approved the amendment of RA 10068, a bill recognizing the Participatory Guarantee System (PGS). They can now certify organic producers, compared to before when only third-party certifying bodies could certify and label organic products.